SHARIA STOCK TRADING IN INDONESIA: PRINCIPLES AND REGULATORY FRAMEWORK: PERDAGANGAN SAHAM SYARIAH DI INDONESIA: PRINSIP DAN KERANGKA REGULASI - Suryadi, Djaka; Alim, Muhammad Nurul (Islamic Banking & Economic Law Studies (I-BEST), 2025)
This study explores the legal foundations and operational mechanisms of sharia-compliant stock trading in Indonesia. Using a normative juridical and qualitative approach, it examines how Islamic principles—particularly the prohibitions of riba, gharar, and maisir—are applied in the Indonesia Stock Exchange. Findings show that stock trading is permissible in Islam when conducted under contracts such as musyarakah and mudharabah, and regulated through fatwas like DSN-MUI No. 80/2011. The Sharia Online Trading System (SOTS) ensures compliance by prohibiting margin trading and short selling. Distinctions from conventional trading lie in sharia screening, real asset backing, and ethical restrictions. This research concludes that Indonesia’s Islamic capital market offers a viable halal investment platform. It recommends enhancing public literacy, transparency in screening criteria, and consistent enforcement to support ethical investing aligned with Islamic law.